Acylglycerol kinase promotes cell proliferation and tumorigenicity in breast cancer via suppression of the FOXO1 transcription factor - Wang, Xi (BioMed Central, 2014)
BACKGROUND: Acylglycerol kinase (AGK) is reported to be overexpressed in multiple cancers. The clinical significance and biological role of AGK in breast cancer, however, remain to be established. METHODS: AGK expression in breast cancer cell lines, paired patient tissues were determined using immunoblotting and Real-time PCR. 203 human breast cancer tissue samples were analyzed by immunochemistry (IHC) to investigate the relationship between AGK expression and the clinicopathological features of breast cancer. Functional assays, such as colony formation, anchorage-independent growth and BrdU assay, and a xenograft tumor model were used to determine the oncogenic role of AGK in human breast cancer progression. The effect of AGK on FOXO1 transactivity was further investigated using the luciferase reporter assays, and by detection of the FOXO1 downstream genes. RESULTS: Herein, we report that AGK was markedly overexpressed in breast cancer cells and clinical tissues. Immunohistochemical analysis showed that the expression of AGK significantly correlated with patients’ clinicopathologic characteristics, including clinical stage and tumor-nodule-metastasis (TNM) classification. Breast cancer patients with higher levels of AGK expression had shorter overall survival compared to patients with lower AGK levels. We gained valuable insights into the mechanism of AGK expression in breast cancer cells by demonstrating that overexpressing AGK significantly enhanced, whereas silencing endogenous AGK inhibited, the proliferation and tumorigenicity of breast cancer cells both in vitro and in vivo. Furthermore, overexpression of AGK enhanced G1-S phase transition in breast cancer cells, which was associated with activation of AKT, suppression of FOXO1 transactivity, downregulation of cyclin-dependent kinase inhibitors p21( Cip1 ) and p27( Kip1 ) and upregulation of the cell cycle regulator cyclin D1. CONCLUSIONS: Taken together, these findings provide new evidence that AGK plays an important role in promoting proliferation and tumorigenesis in human breast cancer and may serve as a novel prognostic biomarker and therapeutic target in this disease.